PENGARUH LATIHAN CORE STABILITY STATIS (PLANK AND SIDEPLANK) TERHADAP KESEIMBANGAN TUBUH PADA PEMAIN PS IKIP MATARAM TAHUN 2019 - Ismail Marzuki; Soemardiawan Soemardiawan (Mandala, 2019)
he focus of the problem in this study was during the training and competition of the PS players. IKIP Mataram is lacking in passing, dribbling, control, shooting, because it is not good in body balance training in body charge, it is easy to fall, as well as in passing, dribbling, control, shooting skills, and therefore the exercise of Static Core Stability Exercise (Plank) And Side Plank) to improve the body balance of PS players. IKIP Mataram. The formulation of the research problem is